Paclitaxel pharmaceutical profiling aiming the optimization of a novel lipid nanotherapy - Carvalho, Ana M. (2016)
Paclitaxel (PTX) is a cytostatic anticancer drug used extensively in wide types of cancer. Due to its lipophilic nature (Kp(water/n-octanol) = 3.54) PTX needs a vehicle for its administration. The current vehicles used to improve PTX solubilisation and administration, however they present toxicity promoting side-effects. Moreover, the lipophilic nature of paclitaxel may have an important role on drug distribution and, consequently, on systemic toxicity, by interacting with amphiphilic molecules, such as lipids and transporter proteins. In this study, it is intended to characterize the interactions of paclitaxel with biological interfaces in a biophysical point of view, in order to predict the absorption, distribution, metabolism, elimination and toxicity (ADMET) of free paclitaxel. Paclitaxel partition coefficient in liposomes/water system under physiological conditions was determined by derivative spectroscopy, paclitaxel effect on membrane viscosity was determined by dynamic light scattering and fluorescence anisotropy, fluorescence quenching studies were used to determine paclitaxel location in cell membrane model (KSV and KD) and determine HAS-paclitaxel binding constant (Kb).